Appendix 7: Details of the 2013 Nutrition for Growth commitment progress assessment - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
Each Nutrition for Growth (N4G) signatory was asked to report on progress made since the 2014 Global Nutrition Report using an online web portal designed for each stakeholder group. When there were clarification issues, we followed up with those who responded, entered final responses into a set of detailed online N4G commitment tracking tables, and made an independent assessment of progress